Strategi Peningkatan Daya Saing PT Borneo Alumina Indonesia pada Bidang Industri Alumina Refinery di Indonesia - Sikki, Nurhaeni; Kuseno, Triandi; Wijaya, Sandra Tiara; Soares, Sebastiao Barreto De Carvalho; Hidayat, Syarif Azwar; Taliudin, Yusuf; Sahrial, Endi (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2025)
The alumina refinery industry in Indonesia faces global challenges and opportunities, necessitating a robust strategic framework to enhance competitiveness. This study analyzes the internal and external factors affecting PT Borneo Alumina Indonesia (BAI) using the IFAS and EFAS frameworks. An IFAS score of 2.81 highlights significant internal strengths, such as state-owned enterprise support, modern technology, and a strategic location, despite weaknesses like reliance on local human resources and high initial operational costs. An EFAS score of 3.32 underscores substantial opportunities from government policies and growing global market demand, outweighing threats such as price fluctuations and geopolitical risks. The analysis places PT BAI in Quadrant I of the SWOT matrix, recommending an aggressive growth strategy through market expansion, product diversification, international collaboration, and infrastructure optimization. This strategic approach is expected to enhance PT BAI’s competitiveness and support sustainable growth in the alumina refining industry.